Os jogos com regras na perspectiva do desenho universal: contribuições à educação matemática inclusiva - Kranz, Cláudia Rosana (2014)
To think about a school that is for everyone has been a challenge for many people connected to education worldwide demanding from researchers of each level of knowledge an association to such effort. The study presented on this paper unites itself to the voices, movements and researches of these scholars, seeking to contribute on building possibilities on which mathematics can be thought and worked on schools in order for every student to learn, whether they have some sort of deficiency, disorders, syndromes or not. This essay has the goal to investigate the possibilities of inclusive pedagogical practices mediated by math games with rules, developed and used throughout the Universal Design perspective; a qualitative research took place with a collaborative methodology that involved managers, teachers and students from a public school situated on the city of Natal/Brazil. On the investigation math games with rules were developed and made according to the Universal Design concept, starting from initial studies which articulated theoretical groundings to the reality of school and the teacher s conceptions. After that, classes using these tools were planned collectively which oriented inclusive pedagogical practices of classes from the 1st to the 4th year of elementary school. Throughout the process many instruments such as: tape recording, video footages, notes from the researcher; the teachers and the students were used for constant work evaluation and also to record the research data. In the end, the data indicated effective contributions of the mediated pedagogical practices by games with rules under the perspective of Universal Design for Inclusive Mathematics Education